2021
DOI: 10.1063/5.0064528
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency and below bandgap anisotropic dielectric constants in α-(AlxGa1−x)2O3 (≤x≤1)

Abstract: A Mueller matrix spectroscopic ellipsometry approach was used to investigate the anisotropic dielectric constants of corundum α-(AlxGa1−x)2O3 thin films in their below bandgap spectral regions. The sample set was epitaxially grown using plasma-assisted molecular beam epitaxy on m-plane sapphire. The spectroscopic ellipsometry measurements were performed at multiple azimuthal angles to resolve the uniaxial dielectric properties. A Cauchy dispersion model was applied, and high-frequency dielectric constants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The trend of the dielectric limit as a function of Al content x is displayed in Fig. 7 (red and green circles) and compared to results of Hilfiker et al 51) (black and gray triangles) and their corresponding bowing fit (black and gray dashed lines).…”
Section: Uv-ellipsometrymentioning
confidence: 92%
“…The trend of the dielectric limit as a function of Al content x is displayed in Fig. 7 (red and green circles) and compared to results of Hilfiker et al 51) (black and gray triangles) and their corresponding bowing fit (black and gray dashed lines).…”
Section: Uv-ellipsometrymentioning
confidence: 92%
“…The phase composition was determined from Ɵ−2Ɵ X-ray diffraction scans, while the crystalline quality was assessed by measurement of the Full Width at Half-Maximum (FWHM) of highresolution, triple-axis symmetric and asymmetric rocking curves. The X-ray reflections used were (0006) and (10)(11)(12)(13)(14)(15)(16)(17)(18). The details can be found in our earlier papers.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed descriptions of experimental setup can be found in our earlier papers. [35][36][37][38][39][40][41] Results and Discussion XRD measurements of the half of the two-inch grown film showed that it is single-phase α-Ga 2 O 3 , with the FWHM of the symmetric (0006) reflection varying between 13 arcminutes and 15 arcminutes, and the FWHM of the asymmetric (10)(11)(12)(13)(14)(15)(16)(17)(18) asymmetric reflection between 14 and 17 arc. minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The α-polytype is a potential solution to extending the stability to higher Al contents and higher temperatures. [2][3][4][5][6][7][8][9][10][11][12] This metastable, corundum crystal structure α-polytype, transforms to the β-polymorph at temperatures above 750 °C-900 °C under equilibrium conditions. 5 Of all reported polymorphs, this phase has the highest optical bandgap with energies ranging between 5.0 eV and 5.3 eV for the binary.…”
mentioning
confidence: 99%